Review on Pharmacological Activities of Turmeric (International Journal of Innovative Research in Engineering & Management, 2023)
Turmeric is a popular spice that is  cultivated all across the Indian subcontinent. Traditional  medicine has utilized turmeric as a treatment for a variety  of ailments, including cough, diabetes, and hepatic  problems. Turmeric and its derivatives have been studied  extensively over the past several decades to determine their  pharmacological properties. Turmeric's primary chemical  component, curcumin, has been shown to have pro,  antioxidant, anti - mutagenic, anti-diabetic, antimicrobial,  cardio-protective, expectorant, and anticancer properties.  This study focuses on the pharmacological effects of  Turmeric, as well as its extracts and potential therapeutic  applications, as well as their safety assessment. Since the  dawn of time, man has used herbal products to treat  illnesses. The Indian subcontinent has a diverse flora,  including both fragrant and medicinal species. In the  Indian traditional medicinal, this vast flora has been  extensively used as a source of numerous medicines.
Keywords: Curcuma Longa Linn; Haridra; Dravyaguna; Medicinal Plant; Turmeric